Clinical analysis of small cell carcinoma of the bladder in Chinese: nine case reports and literature reviews. Issue 1 (December 2017) - Chen, Zhi; Liu, Qingquan; Chen, Ruibao; Liu, Zhuo; Li, Mingchao; Ling, Qing; Wu, Licheng; Yang, Jun; Liu, Xiaming; Wang, Tao; Hu, Zhiquan; Guo, Xiaoling; et al.
Abstract Background Small cell carcinoma of the bladder (SCCB) is a kind of rare and highly aggressive tumor that is present in an advanced stage and has a propensity for early metastasis. The main presenting symptom of SCCB is hematuria. Surgery, chemotherapy, and radiotherapy, either alone or as ﻿a﻿ part of combined therapy, have been used as the treatment. The aim of this study is to present our experience with 9 SCCB patients who were treated with different modalities and to share the findings upon reviewing the literatures for patients with SCCB reported in 56 literatures in Chinese. Methods We retrospectively evaluated 9 patients with SCCB from February 1980 to January 2014 in Tongji Hospital, Huazhong University of Science and Technology. The general characteristics, clinical manifestations, the pathological and immunohistochemical characteristics, treatment options, and prognostication in those eligible manuscripts were analyzed. In order to gain a better understanding of the clinical features of SCCB, another 119 cases reported in 56 articles were reviewed together (from January 1979 to March 2014). And a retrospective analysis was performed. Results All the 9 cases in Tongji Hospital were successfully operated, and the tissue samples were sent for pathological examination. All the tumor tissues contained small cell carcinoma components. 4 cases coexisted with other histologic types of bladder cancers, and 2 out of the 9 cases had three different cell components. All the patients had muscle invasion, and 4 cases showed lymph nodes metastasis, 3 cases showed invasion of neighboring structures (seminal vesicle or uterus), and 1 case was highly suspected of liver metastasis. Immunohistochemistry results showed that PCK, Syn, NSE, and CD56 were all positive, but LCA was negative. After operations, 3 patients underwent chemotherapy and only 1 patient received postoperative radiotherapy. Patients were followed up, ranging from 3 to 84 months and the median survival time was 33 months. The leading cause of death was tumor recurrence or metastasis, while 2 patients are still alive. According to the published literature, the pathological stage, immunohistochemical markers, and survival curves of all the 128 cases were also retrospectively analyzed. Conclusions SCCB is different from transitional cell carcinoma (TCC) of the bladder. It has its unique cytology, immunohistochemistry, and ultrastructural features. Its diagnosis relies on pathological examination and immunohistochemistry. The current main treatment for SCCB is surgery combined with chemotherapy. Since the disease develops early metastasis easily, the overall prognosis of this cancer is poor. Further research need to clarify the molecular pathogenesis so that novel therapies can be developed for this rare cancer.